2014
DOI: 10.3944/aott.2014.13.0150
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of coenzyme Q10 (CoQ10) on steroid-induced osteonecrosis in rats

Abstract: Coenzyme Q10 may be useful as a preventing agent in steroid-induced ONFH. Inhibited oxidative stress is a possible mechanism for this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The toll-like receptor 4 (TLR4) pathway was implicated in SONFH by Okazaki et al [48] and Tian et al [49], who found that corticosteroids SONFH by disturbing the immune response via TLR4 signaling pathway. Subsequently, Erkam Komurcu et al [50] and Miyata et al [51] found that coenzyme Q10 prevented SONFH by reducing oxidative stress. Pentosan, a semisynthetic polysulfated xylan appears to reduce the incidence of ONFH in SHRSP by improving lipid metabolism and decreasing oxidative stress.…”
Section: Ratmentioning
confidence: 99%
“…The toll-like receptor 4 (TLR4) pathway was implicated in SONFH by Okazaki et al [48] and Tian et al [49], who found that corticosteroids SONFH by disturbing the immune response via TLR4 signaling pathway. Subsequently, Erkam Komurcu et al [50] and Miyata et al [51] found that coenzyme Q10 prevented SONFH by reducing oxidative stress. Pentosan, a semisynthetic polysulfated xylan appears to reduce the incidence of ONFH in SHRSP by improving lipid metabolism and decreasing oxidative stress.…”
Section: Ratmentioning
confidence: 99%
“…3,4 Many antioxidants have proven to be effective correspondence: Qiugen Wang Trauma center, shanghai general hospital, shanghai Jiaotong University school of Medicine, 650 Xin songjiang road, shanghai 201620, china Tel +86 1 331 198 6527 email wangqiugen@126.com in therapy for steroid-induced osteonecrosis in rat models. 5,6 It is reported that selenium (Se), an essential micronutrient in humans and animals with a wide range of biologic functions, 7 could suppress oxidative stress and serves as a reactive oxygen species (ROS) scavenger. [8][9][10][11] In some cases, a deficiency of Se could induce oxidative stress and endoplasmic reticulum stress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been hypothesized that osteonecrosis is produced by the ischemic change accompanying the compartment pressure load in the marrow, where degeneration and necrosis may occur simultaneously with oxidative stress16. Besides, antioxidants such as Coenzyme Q10 (CoQ10)17 and hydrogen-rich saline18, have already been proved to be therapeutic for steroid-induced osteonecrosis in rats. While stem cell factor (SCF)19 and grape seed proanthocyanidin proved protective by reducing oxidative stress20.…”
mentioning
confidence: 99%